STRATEGI PEMASARAN EKSPOR PADA UMKM KERUPUK TIGA WARNA DALAM MEMASUKI PASAR GLOBAL - Diondi Nugroho; Enna Marliana; Friza Pertiwi; Nanda Dewi Anggraeni (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2022)
The purpose of this study is to determine the export marketing strategy of three-color cracker SMEs in entering the global market. The method used in this study uses a qualitative approach with data collection techniques through interviews and observations. The results of this study indicate that the export marketing strategies that can be used for three-color crackers in entering the global market are as follows: a. Knowing the target market to be achieved, b. considering the scale of the business that you want to target, such as financing and consumer interest who will buy three-color crackers, c. know and observe the regulations of the destination country, d. form partnerships as needed.